2009
DOI: 10.1175/2008waf2007103.1
|View full text |Cite
|
Sign up to set email alerts
|

A Case Study of Severe Winter Convection in the Midwest

Abstract: Between 2100 UTC 11 February 2003 and 0200 UTC 12 February 2003, a line of thunderstorms passed swiftly through parts of eastern Iowa and into north-central Illinois. Although this storm somewhat resembled a warm season, line-type mesoscale convective system, it was unique in that the thunderstorm winds exceeded the severe criterion (50 kt; 25.7 m s 21 ) during a snowburst. While the parent snowband deposited only 4 cm of snow, it did so in a short period and created a treacherous driving situation because of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
27
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(30 citation statements)
references
References 22 publications
3
27
0
Order By: Relevance
“…The total measured snow accumulation for the day at CYOW was 3.6 cm, very similar to the precipitation accumulation in Illinois in the event studied by Pettegrew et al (2009). The total measured snow accumulation for the day at CYOW was 3.6 cm, very similar to the precipitation accumulation in Illinois in the event studied by Pettegrew et al (2009).…”
Section: Case Overviewsupporting
confidence: 74%
See 4 more Smart Citations
“…The total measured snow accumulation for the day at CYOW was 3.6 cm, very similar to the precipitation accumulation in Illinois in the event studied by Pettegrew et al (2009). The total measured snow accumulation for the day at CYOW was 3.6 cm, very similar to the precipitation accumulation in Illinois in the event studied by Pettegrew et al (2009).…”
Section: Case Overviewsupporting
confidence: 74%
“…4e). Pettegrew et al (2009) found substantial low-level (925 hPa) frontogenesis associated with the snow burst in Illinois. By t 5 13 h (Fig.…”
Section: Dynamic and Thermodynamic Analysismentioning
confidence: 93%
See 3 more Smart Citations